Algeria : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper examines the options and strategies for designing a fiscal framework for Algeria. It suggests that given the expected lifetime of hydrocarbon reserves, ensuring long-term sustainability and saving for future generations should be the priorities of fiscal policy. The fiscal framework also needs to be supported by an adequate institutional arrangement. Overall, the reserves management capacity should be strengthened. The budget law needs to incorporate the new fiscal rule and define the way to enforce it. For the sake of smooth transition, the management of the sovereign wealth fund should be the responsibility of the central bank, which already has the capacity and experience in reserves management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet